2021
DOI: 10.1002/humu.24200
|View full text |Cite
|
Sign up to set email alerts
|

Beyond copy number: A new, rapid, and versatile method for sequencing the entire SMN2 gene in SMA patients

Abstract: Spinal muscular atrophy (SMA) is caused by bi-allelic loss or pathogenic variants in the SMN1 gene. SMN2, the highly homologous copy of SMN1, is considered the major phenotypic modifier of the disease. Determination of SMN2 copy number is essential to establish robust genotype-phenotype correlations and predict disease evolution, to stratify patients for clinical trials, as well as to define those eligible for treatment. Discordant genotype-phenotype correlations are not uncommon in SMA, some of which are due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…Most gene conversion events occur at the canonical c.840C>T nucleotide difference at exon 7 [ 59 , 60 ]. There are, however, at least 15 other paralogous structural variants (PSVs) between SMN1 and SMN2 ( Figure 3 ; [ 60 , 108 , 120 , 135 , 136 ]). Gene conversion events at exon 8 ( SMN2c.1155G>A ) as well as those within intron 6 ( SMN2c.835-44G>A ) and intron 7 ( SMN2c.888+100A>G and SMN2c.888+215A>G ) have been observed in SMA, as well as in control populations [ 127 , 129 , 133 ].…”
Section: Smn1 To Smn2 Gene Conversions and Partial Deletionsmentioning
confidence: 99%
“…Most gene conversion events occur at the canonical c.840C>T nucleotide difference at exon 7 [ 59 , 60 ]. There are, however, at least 15 other paralogous structural variants (PSVs) between SMN1 and SMN2 ( Figure 3 ; [ 60 , 108 , 120 , 135 , 136 ]). Gene conversion events at exon 8 ( SMN2c.1155G>A ) as well as those within intron 6 ( SMN2c.835-44G>A ) and intron 7 ( SMN2c.888+100A>G and SMN2c.888+215A>G ) have been observed in SMA, as well as in control populations [ 127 , 129 , 133 ].…”
Section: Smn1 To Smn2 Gene Conversions and Partial Deletionsmentioning
confidence: 99%
“…More studies are needed to determine which structure is correct or if both orientations are present in the population. Given that SMN2 was originated from SMN1, their sequences only differ in 16 paralogous sequence variants (PSVs), which represent a total of 20 different nucleotides between both genes (15 SNVs and 1 indel) [10] as represented in Figure 1. The PSV c.840C>T, located in exon 7, causes exon skipping in the majority of SMN2 pre-mRNA transcripts resulting in a truncated, nonfunctional and rapidly degraded protein that is not able to oligomerize (SMN-∆7) [11] and can only produce the complete functional protein in 10-15% of cases [12][13][14].…”
Section: Sma Is a Disease Of Two Genes A Determinant Smn1 And A Modifier Smn2mentioning
confidence: 99%
“…In addition, it has been postulated that this allele has originated from a common ancestor by haplotype analysis [39]. The second variant classified as a positive modifier is the variant c.835-44A>G, located in intron 6, and it is one of the 16 PSVs described between SMN1 and SMN2 [10,40]. Wu et al (2017) demonstrated that this transition decreases the affinity of the RNA-binding protein HuR, which acts as a splicing repressor, increasing in~20% the SMN2 exon 7 inclusion [38].…”
Section: The Known Validated Genotypesmentioning
confidence: 99%
See 2 more Smart Citations